2019
DOI: 10.3390/ijms20225572
|View full text |Cite
|
Sign up to set email alerts
|

HLA-F Allele-Specific Peptide Restriction Represents an Exceptional Proteomic Footprint

Abstract: Peptide-dependent engagement between human leucocyte antigens class I (HLA-I) molecules and their cognate receptors has been extensively analyzed. HLA-F belongs to the non-classical HLA-Ib molecules with marginal polymorphic nature and tissue restricted distribution. The three common allelic variants HLA-F*01:01/01:03/01:04 are distinguished by polymorphism outside the peptide binding pockets (residue 50, α1 or residue 251, α3) and are therefore not considered relevant for attention. However, peptide selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…In all investigations concerning the interaction between HLA-F and its cognate immune receptors, only HLA-F*01:01 and HLA-F*01:01 OC were examined [5,6]. Our peptide sequence analysis from HLA-F allelic variants featured hemoglobin subunit beta (HBB) peptide (VNVDEVGGEALGR) as dominant and shared [8]. Since HBB is upregulated during HIV infection and presented by all three allelic variants of HLA-F, we suggest that peptide presentation is involved in the obstacle of reducing interaction between HLA-F and KIR3DS1 in HIV infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In all investigations concerning the interaction between HLA-F and its cognate immune receptors, only HLA-F*01:01 and HLA-F*01:01 OC were examined [5,6]. Our peptide sequence analysis from HLA-F allelic variants featured hemoglobin subunit beta (HBB) peptide (VNVDEVGGEALGR) as dominant and shared [8]. Since HBB is upregulated during HIV infection and presented by all three allelic variants of HLA-F, we suggest that peptide presentation is involved in the obstacle of reducing interaction between HLA-F and KIR3DS1 in HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, polymorphism of other HLA-Ib molecules HLA-E and HLA-G that should also not interfere with peptide selection, binding, and presentation impacts their immune function significantly [22,34]. Recently, it has been shown that the polymorphism of HLA-F allelic variants does not influence peptide features of presented peptides [8]. The pHLA structure of HLA-F differs from the classical pHLA structure [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations